PRELIMINARY STUDIES OF ANALYZING MISCONCEPTION AND SCIENTIFIC ARGUMENTATION USING DIAGNOSTIC QUESTION CLUSTERS (DQCS) OF MOLECULAR GENETICS CONCEPT - Lela Nurlaila; Siti Sriyati; Riandi Riandi (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2018)
This study aimed to analyze the misconceptions and argumentation ability Biology education students using diagnostic question clusters on the concept of molecular genetics. In addition, this study aims to look at the pattern of misconceptions tendencies and scientific argumentation ability of students accompanied by the factors supporting the occurrence of misconceptions and arguments student achievement levels. As this study focused on the concept of molecular genetics which includes the concept of genes, chromosomes, DNA, and protein synthesis. This research was conducted with the descriptive research method and the sample using purposive sampling techniques. The subjects were biology education students of Islamic University of Sunan Gunung Djati Bandung who attended the lectures of genetics in the academic year 2014/2015. The instrument used is a matter of diagnostic question clusters (DQCs) which covers a combined essay and multiple choice questions, learning observation sheet, and interview guidelines used to determine the factors that cause the occurrence of misconceptions and what degree of scientific argumentation ability students. The ability of the scientific arguments that will be analyzed is the ability to claim, warrant, backing, and rebutal (Toulmin, 1984).